Imamah: Kajian Doktrin Syi’ah dan Perdebatan Pemikiran Islam Klasik - Ris'an Rusli (Pusat Penelitian dan Penerbitan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Raden Fatah Palembang, 2015)
This article is the result of research that reviewing the concept of Imamah according to the Shiite sect. The concept of Imamah according to the Shiite sect, including: Ithna 'Asyariyah Shiite, and Ghulat Shiite. Ithna 'Asyariyah Shiite assume that the position as Imam was in the hands of their twelve Imams, starting from Ali ibn Abi Talib and the last twelfth Imam (Muhammad ibn Hasan who was named as al-Mahdy). To support this Imamah faith they create other teaching as complementary, including: al-'Ishmah, al-Mahdy and al-Raj'ah and al-Taqiyyah. While Ghulat Shiites called extreme groups because of their attitude exaggerated against their Imams. So has the opinion that out of limitsabout tgheir Imam as a creature and set the properties of divinity, which resemble God or equate God with creatures.